Consciousness loss during epileptogenesis: implication for VLPO-PnO circuits - Feng, Maohui (Int J Physiol Pathophysiol Pharmacol, 2017)
There is a growing concern about consciousness loss during epileptic seizures. Understanding neural mechanisms could lead to a better comprehension of cerebral circuit function in the control of consciousness loss in intractable epilepsy. We propose that ventrolateral preoptic area (VLPO)- PnO (nucleus pontis oralis) circuits may serve a major role in the loss of consciousness in drug-refractory epilepsy. Future behavioural and neuroimaging studies are clearly needed to understand the functional connectivity between the VLPO and PnO during loss of consciousness in drug-refractory epilepsy, to greatly prevent unconsciousness in this disorder and improve the quality of life in patients with intractable epilepsy.